Simultaneous determination of macrolides in water samples by solid-phase extraction and capillary electrophoresis - Pavlović Dragana Mutavdžić; Babić Sandra; Čizmić Mirta; Sertić Miranda; Pinušić Tea (Acta Pharmaceutica)
Solid-phase extraction (SPE) coupled with capillary electrophoresis (CE) for the determination of macrolide antibiotics (azithromycin, clarithromycin, roxithromycin, tylosin) and tiamulin in water samples was described in this article. These compounds were extracted with different types of sorbents ( Oasis HLB, C18, C8, SDB, and Strata-X) and different masses of sorbents (60 mg, 200 mg, and 500 mg) using different organic solvents (methanol, ethanol, and acetonitrile) and different pH values of water samples (pH 7.00, 8.00, and 9.00). It was found that the highest extraction efficiency of the studied compounds was obtained with 200 mg/3 mL C18 cartridges with methanol as eluent at pH 9.00 of the water sample. The developed SPE-CE method for macrolide antibiotics and tiamulin was validated for linearity, precision, repeatability, the limit of detection (LOD), the limit of quantification (LOQ), and recovery. Good linearity was obtained in the range of 0.3–30 mg L−1 depending on the drug, with correlation coefficients higher than 0.9958 in all cases except clarithromycin (0.9873). Expanded measurement uncertainties were calculated for each pharmaceutical, accounting for 20.31 % (azithromycin), 38.33 % (tiamulin), 28.95 % (clarithromycin), 26.99 % (roxithromycin), and 21.09 % (tiamulin). Uncertainties associated with precision and calibration curves contributed the most to the combined measurement uncertainty. The method was successfully applied to the analysis of production waste-water from the pharmaceutical industry.